Umbilical discharge - An extremely rare presentation - Mishra, Ipseet; Haldar, Sudip; Paul, Souvik; Dutta, Purnendu (Indian Journal of Case Reports, 2020)
Umbilical discharge and dermoid cyst of ovary are quiet commonly encountered problems in the outpatient departments. However, dermoid cyst presenting as a cause of umbilical discharge is extremely rare, and we could find only one case reported in literature so far. A 20-year-old lady presented with painful umbilical swelling and purulent discharge from umbilicus for the last 2 months. A 1 cm×2 cm sprouting granulation tissue with purulent discharge was found at the umbilicus with surrounding erythema. The dilemma in diagnosis was not resolved with routine investigations and imaging studies. On surgical exploration, a fistulous tract was found extending from the umbilicus to the enlarged right ovary. The diagnosis of benign teratoma of ovary with sinus tract up to umbilicus was made on histopathology. The rarity of this case makes its reporting further relevant, considering the differential diagnosis of umbilical discharge or presentations of dermoid cyst of ovary.